Use of ICT Integrated Pedagogy in English Language Teaching: Readiness and Challenges - Kadel, Purna Bahadur; Joshi, Bishow Raj (Nepal Journal of Multidisciplinary Research, 2025)
Background: Information Communication Technology (ICT) integrated pedagogy is an essential approach to improve learning achievement, particularly language skills, vocabulary, grammar and 21st century skills at community schools. Objectives: This study attempted to explore whether English language teachers are ready to use ICT integrated pedagogy in teaching English at the secondary level and to identify the challenges of English language teachers in integrating ICT in teaching English. Methods: To deal with the research objectives, a hermeneutic phenomenological research design was used to accomplish this study. The lived experiences and reflections of English language teachers were required to find out the relevance of ICT integrated pedagogy and their readiness to employ ICT tools for enhancing learning achievement. Eight English teachers were selected through a judgmental non-random sampling procedure. The in-depth interview and classroom observation were administered to elicit the required lived experiences of English language teachers regarding their readiness and challenges of applying ICT integrated pedagogy to teach language skills, vocabulary, and grammar to the EFL learners in the context of Nepal. Findings: The findings of this study were the inevitability of engagement and motivation, the development of 21st century skills in learning through ICT literacy, the lack of ICT devices and e-learning workshops and training in developing language skills and aspects. Conclusion: ICT integrated pedagogy is an essential approach to engage the students to enhance learning achievement in community schools in Nepal. This approach helps the ELT teachers of basic and secondary level to promote their 21st century skills such as critical thinking skills, collaborative skills and digital literacy in the context of Nepal. Novelty: The implication of this study helps the policy makers, teachers and students to be aware of the benefits of digital pedagogy to promote learning achievement of the learners and professional growth of ELT teachers through digital pedagogy.